Analysis of Water Quality at Way Belerang Simpur Hot Spring Tourist Site in Kecapi Village, Kalianda District, South Lampung Regency, Lampung Province - Zidni Ilman Navia; Saputri, Dwijowati Asih; Yurika Septi (WISE Pendidikan Indonesia, 2024)
Way Belerang Simpur is a sulfur-containing hot spring that serves as a popular tourist destination for hot spring baths. This study aims to evaluate the water quality of the spring using physical, chemical, and biological parameters. Water samples were taken from three points: the source (Point 1), the bathing area (Point 2), and the downstream flow (Point 3). The parameters analyzed include temperature, pH, dissolved oxygen (DO), odor, hydrogen sulfide (H2S), biochemical oxygen demand (BOD), chemical oxygen demand (COD), and total coliform bacteria. Standard testing methods such as mercury thermometers, pH meters, spectrophotometry, and SNI protocols were used. Results show that temperature and odor meet national standards for safe water, but pH levels were highly acidic, exceeding acceptable limits for public bathing. DO levels were adequate to support aquatic life, while BOD, COD, and H2S were within acceptable limits. The biological analysis revealed very low levels of total coliform bacteria, making the water microbiologically safe. Overall, the water quality at Way Belerang Simpur is suitable in terms of contamination levels but presents risks due to its high temperature and low pH, especially for prolonged exposure.